GE_GERICHTE C/7893/2017 vom 15. Juli 2019 - GE Cour de justice (2019)
BAIL À LOYER;NOUVEAU MOYEN DE PREUVE;NOTORIÉTÉ;RÉSILIATION ABUSIVE;DROIT D'ÊTRE ENTENDU;PROLONGATION DU BAIL À LOYER;LOYER | CO.271.al1; CO.272.al1